2017
DOI: 10.1017/s0003055417000119
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Skill Development and Adult Political Participation

Abstract: Recent child development research shows that the psychosocial or noncognitive skills that children develop—including the ability to self-regulate and integrate in social settings—are important for success in school and beyond. Are these skills learned in childhood also important for adult political behaviors like voting? In this article, I use a unique school-based 20-year field experiment to explore whether children who develop psychosocial skills early on are more likely to vote in adulthood than those who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 63 publications
(101 reference statements)
3
48
0
1
Order By: Relevance
“…when one turns 18), one's interest in politics-one of the strongest predictors of whether one votes (Veba, Schlozman, and Brady 1995)-tends to exhibit remarkable levels of intertemporal stability and rigidity to targeted intervention. Furthermore, the cognitive and non-cognitive skills important for voting may solidify over time (Holbein 2017); as a result, resource investments designed to target these skills may have less of an effect on voter turnout than earlier investments. Consistent with this view, some research has shown that voting patterns tend to be persistent over time (Fujiwara, Consistent with human capital models of other adult behaviors, one might expect that if income does matter for voting it may matter more-so for income accumulated earlier in the life course rather than later.…”
Section: A Human Capital-based Framework Of Votingmentioning
confidence: 99%
“…when one turns 18), one's interest in politics-one of the strongest predictors of whether one votes (Veba, Schlozman, and Brady 1995)-tends to exhibit remarkable levels of intertemporal stability and rigidity to targeted intervention. Furthermore, the cognitive and non-cognitive skills important for voting may solidify over time (Holbein 2017); as a result, resource investments designed to target these skills may have less of an effect on voter turnout than earlier investments. Consistent with this view, some research has shown that voting patterns tend to be persistent over time (Fujiwara, Consistent with human capital models of other adult behaviors, one might expect that if income does matter for voting it may matter more-so for income accumulated earlier in the life course rather than later.…”
Section: A Human Capital-based Framework Of Votingmentioning
confidence: 99%
“…Historically, studies have found that developmental experiences prior to adulthood have enduring effects on political orientation across the life span (Sears & Brown, 2013). Questions regarding the nature and persistence of childhood influences on political orientation have resurfaced (Astuto & Ruck, 2010;Holbein, 2017;Patterson et al, 2019;Torney-Purta, 2017). Recent work in political psychology has conceptualized ideology as motivated social cognition, reframing individual political differences in terms of personality, needs, attitudes, and beliefs (Jost, Glaser, Kruglanski, & Sulloway, 2003;Jost, 2017).…”
mentioning
confidence: 99%
“…Hence, along with experimental evidence on the mediating role of psychosocial functioning (i.e. grit, see Holbein, 2017), this study suggests to consider in these discussions basic psychological needs as a potential common cause of political participation and its various correlates.…”
Section: Discussionmentioning
confidence: 66%
“…Specifically, research on various life domains revealed the satisfaction of basic psychological needs as common influence of those outcomes that also go along with political engagement (i.e., pro-social behavior and social trust, see: Bougher, 2017; Padilla-Walker, 2014; moral reasoning capacities, see: Grolnick, Deci, & Ryan, 1997, 153f; cognitive capabilities, see: Grolnick & Ryan, 1987;Ryan, Connell, & Plant, 1990; social adaptability, see: Kasser, Koestner, & Lekes, 2002;Laurin & Joussemet, 2017 and occupational performance, see: Deci, Olafsen, & Ryan, 2017). Despite an upsurge of research highlighting the importance of non-political experiences for the development of political engagement (e.g., Galais, 2018;Holbein, 2017;Shani, 2009), political socialization research has not considered the concept of basic psychological needs in examining the origins of political engagement so far. Considering the ubiquitous influence of basic needs for attainments in various life domains and their association with political participation, need-related experiences may also play a role in shaping political engagement.…”
Section: Political Engagement's Non-political Roots: Examining the Romentioning
confidence: 99%